Autism Research: An Objective Quantitative Review of Progress and Focus Between 1994 and 2015 - Whyatt, Caroline P.; Torres, Elizabeth B. (Frontiers in Psychology, 2018)
The nosology and epidemiology of Autism has undergone transformation following consolidation of once disparate disorders under the umbrella diagnostic, Autism Spectrum Disorders (ASD). Despite this re-conceptualization, research initiatives including the NIMH’s Research Domain Criteria and Precision Medicine, highlight the need to bridge psychiatric and psychological classification methodologies with biomedical techniques. Combining traditional bibliometric co-word techniques, with tenets of graph theory and network analysis, this article provides an objective thematic review of research between 1994-2015 to consider evolution and focus. Results illustrate growth in Autism research since 2006, with nascent focus on physiology. However, modularity and citation analytics demonstrate dominance of subjective psychological or psychiatric constructs, which may impede progress in the identification and stratification of biomarkers as endorsed by new research initiatives.